Mobile space data progressive transmission based on P2P technology - Zhou, Hong; Xu, Danhai; Wang, Yingzhi (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2014)
The new demand of current mobile GIS development and mobile spatial information data distribution are analyzed. On the basis of large volumes of data in mobile environments, the instability of the wireless signal data transmission and other aspects are discussed. The peer to peer network (P2P) technology is introduced to solve the problem of client subject to the influence of network quality and large-scale spatial data display time-consuming in a wireless network environment, and it effectively improves the efficiency and stability of the mobile GIS system. The experiment shows that cache download of the the P2P service and the progressive transmission of the map service can effectively shorten the response time of user access, and reduce the probability of the data lost due to the network instability.